Outcomes of systemic anticoagulation with bivalirudin for Impella 5.0. Issue 10 (October 2021) - Fabrizio, Carly; Levito, Marissa N; Rivosecchi, Ryan; Bashline, Michael; Slocum, Brittany; Kilic, Arman; Toma, Catalin; Murray, Holt; Ramanan, Raj; Fowler, Jeffrey; Hickey, Gavin W; Horn, Edward T
Temporary mechanical circulatory support (tMCS) devices are used for the management of cardiogenic shock. The Impella 5.0 (Abiomed; Danvers, MA) (IMP5) is a commonly used, surgically implanted, tMCS device that requires systemic anticoagulation and purge solution to avoid pump failure. To avoid heparin-induced thrombocytopenia (HIT) from unfractionated heparin (UFH) use, our program has explored the utility of bivalirudin (BIV) for systemic anticoagulation in IMP5. This single center, retrospective study included patients supported on IMP5 with BIV based AC. The efficacy and safety end points were recovery, bridge to left ventricular assist device (LVAD), cardiac transplant (HTX), or death as well as clinically significant bleeding, incidence of Tissue Plasminogen Activator (tPA) use for suspected pump thrombosis, stroke, and device failure. There were 31 patients included, and 26 (84%) received BIV purge solutions. The median duration of IMP5 was 6 (IQR 4–10) days. Most patients were bridged to LVAD (39%, 12); 16% (5) were bridged to HTX, 16% (5) recovered, and 29% (9) died. One patient (3%) suffered from ischemic stroke and 12% (4) patients developed clinically significant bleeding. tPA was administered to 8 (26%) patients. Logistic regression analysis demonstrated that duration of IMP5 was a significant predictor of tPA use (OR 1.28; 95% Confidence Interval 1.04–1.56). There were no cases of pump failure. Our experience highlights the feasibility of utilizing BIV for routine AC use in IMP5.